MODIFIKASI FURNACE MENGGUNAKAN SISTEM VAKUM (PERBANDINGAN KONDISI VAKUM DAN TANPA VAKUM DITINJAU DARI HASIL KLINKER) - Junaidi, Robert (KINETIKA, 2018)
Furnace is a device used to heat a material and change its shape or change its properties due to heat treatment of the material. Modification of the 1200oC furnace design with a vacuum system was performed using a khantal heating element with a thermocouple type K and refractory material type SK-34 which has a resistance at 1300oC. The vacuum system is designed to use a vacuum pump as a vacuum in the heating chamber and use glasswool as a heat damper from the air to be dived. The performance test of the tool in terms of the clinker chemical content formed by variation of the composition of the addition of high limestone ranging from 5–40% with a 5% increase of the total raw mix. The clinker formation process was carried out on vacuum conditions and without vacuum at temperature 1200oC for 2 hours. From each clinker formed, the levels of each chemical content are C2S, C3S, C3A and C4AF using X-Ray Diffraction (XRD) analysis. The results of the clinker chemical content produced in vacuum conditions differed from those produced in conditions without vacuum